2002
DOI: 10.1046/j.1365-2982.2002.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Subdiaphragmatic vagal afferent innervation in activation of an opioidergic antinociceptive system in response to colorectal distension in rats

Abstract: In a number of different experimental paradigms of somatic pain, there is evidence for a vagally mediated antinociceptive system. This pathway probably involves opioid mechanisms. However, whether this pathway is activated in visceral pain or if it involves subdiaphragmatic vagal afferents is unclear. The aim of the present study was to determine whether subdiaphragmatic vagal afferents mediate antinociception in response to a visceral stimulus and whether this involves an opioid pathway. Colorectal distension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 30 publications
9
26
0
Order By: Relevance
“…However, it is possible that inflammatory changes modulated in the vagally innervated proximal colon result in changes in the enteric nervous system in the remainder of the colon (29), resulting in a reduction in acetylcholine release. This may account for the effect of vagotomy on colitis seen in this and other studies (20,26,27,30). We also demonstrate the same profile of results using the maternal deprivation model.…”
Section: Discussionsupporting
confidence: 88%
“…However, it is possible that inflammatory changes modulated in the vagally innervated proximal colon result in changes in the enteric nervous system in the remainder of the colon (29), resulting in a reduction in acetylcholine release. This may account for the effect of vagotomy on colitis seen in this and other studies (20,26,27,30). We also demonstrate the same profile of results using the maternal deprivation model.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the opioid receptor antagonist naloxone did not affect the overall response or the response attenuation to CRD in C57BL/6 mice at any dose tested, further supporting that the opioid system is most likely not involved in the attenuation of the VMR seen in mice. That naloxone did not affect the VMR to CRD conflicts with results in rats, which however do not display a transient response, 17,18 but is similar to results obtained in mice. 25,26 The difference seen between rats and mice may reflect alternative linkages between stress responses and visceral pain in these two species.…”
Section: Discussionsupporting
confidence: 75%
“…It has been proposed that there is an ongoing opioid-driven tone in the gastrointestinal sensory system, as naloxone increased the VMR to CRD in both naïve and trinitro-benzenesulphonic acid-treated rats. 17,18 Therefore, in the current study, the magnitude and duration of the transient VMR was investigated in detail in order to evaluate whether endogenous opioids are involved in the attenuation of the VMR in mice. We also evaluated whether the opioid system in general is involved in the attenuation mechanism of the VMR by giving the prototypic nonspecific opioid receptor antagonist naloxone.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that a slight but insignificant increase in the VMR to noxious gastric distension after chronic vagotomy (51). However, other studies have shown that vagotomy blunts the VMR to upper cervical esophageal distensions (22) and significantly enhanced the VMR to tonic CRD in conscious rats (17). In this study, we demonstrated that chronic subdiaphragmatic vagotomy decreases the threshold and enhances the VMR to all grades of CRD (470, 106, 51, and 54% increases in VMR to CRD at 20, 40, 60, and 80 mmHg, respectively).…”
Section: Discussionmentioning
confidence: 97%